Tiempos de Cuarentena con la Innovación e Implementación de las Ayudas Tecnologicas en la Enseñanza de las Matemáticas (2023)
The purpose of this document is to publicize the problems of innovation and implementation of technological aids in the teaching of mathematics, according to the bibliographic research it was determined that currently mathematics is the area with the greatest complexity in the implementation of technological aids, since the move from the traditional method to the virtual, It is a process that is difficult for learners and teachers to adapt. For teachers of the XXI century, this transition has disturbed the educational community due to the management of multiple learning methodologies, which left in view that during the period of the COVID-19 pandemic, it was evident that students did not advance in their training process, to which for the return of classes they had to use different strategies to be able to level their students according to the current grade in which These were, therefore it is considered that mathematics continues to be an area of traditional methodology and not so much virtual.